The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1103/physrevmaterials.3.024412
|View full text |Cite
|
Sign up to set email alerts
|

Effect of phonon anharmonicity on ferroelectricity in EuxBa1xTiO3

Abstract: Investigating the competition between ferroelectric ordering and quantumfluctuations is essential to tailor the desired functionalities of mixed ferroelectric and incipient ferroelectric systems, like, (Ba,Sr)TiO3 and (Eu,Ba)TiO3. Recently, it has been shown that suppression of quantum fluctuations increases ferroelectric ordering in (Eu,Ba)TiO3 and since these phenomena are coupled to crystallographic phase transitions it is essential to understand the role of phonons. Here, we observe that the unusual temper… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 43 publications
1
21
0
Order By: Relevance
“…Along these lines, we like to stress again that the scope of the presented method goes beyond thermal transport and phase transition mechanisms, and potentially applies to any phenomenon governed by anharmonic effects such as free energies [53], thermal expansion [54], thermal stability [55], defect formation [56,57], ferroelectricity [58], and electronphonon coupling [59]. Further investigations are expected to reveal useful relationship between σ A and these target properties, as the thermal conductivities example above showcases.…”
Section: Discussionmentioning
confidence: 86%
“…Along these lines, we like to stress again that the scope of the presented method goes beyond thermal transport and phase transition mechanisms, and potentially applies to any phenomenon governed by anharmonic effects such as free energies [53], thermal expansion [54], thermal stability [55], defect formation [56,57], ferroelectricity [58], and electronphonon coupling [59]. Further investigations are expected to reveal useful relationship between σ A and these target properties, as the thermal conductivities example above showcases.…”
Section: Discussionmentioning
confidence: 86%
“…Based on the information provided in Poojitha et al [ 28 ] we suspect that the broad bands are the result of the high laser power used in these studies. Figure S3 clearly evidences the effect of overheating on our samples: starting from a featureless Raman spectrum, consistent with the cubic space group, broad bands appear with increased laser power, similar to those observed in Poojitha et al [ 28 ] (which remain when laser power is reduced). From this observation we conclude that the observed modes detected are caused by oxidation of the ETO.…”
Section: Resultsmentioning
confidence: 84%
“…Recently, an experimental study of ETO polycrystalline samples [ 28 ] revealed broad Raman bands even at room temperature (as in SrTiO 3 [ 7,8 ] ), which were almost temperature independent. Based on the information provided in Poojitha et al [ 28 ] we suspect that the broad bands are the result of the high laser power used in these studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They have attributed the observed correlation between magnetic and dielectric responses to the possible spin-phonon coupling in 15R-BaMnO3. Since phonons play a major role in ferroelectric materials [16][17][18], one may expect them to have an equally important role in the magnetoelectric multiferroics too. A detailed understanding of the phonons and their coupling is, therefore, extremely important as it extends the opportunity to engineer new functionalities in transition metal oxides such as BaMnO3 and others.…”
Section: Introductionmentioning
confidence: 99%